Social identity of the population as a criterion for the organisation of public authority at the local level in the Russian Federation - Praskova, Svetlana V. (Journal of the Belarusian State University. Law, 2023)
The author of the article notes that after the constitutional reform of 2020 in Russia the issue of the organisation of public authority at the local level became actual. Whereas previously there had been much debate about the types of municipalities and the requirements imposed on them, now the expediency of maintaining local self-government raises doubts and the question about its replacing by local government is posed. In this context, the author proposes to approach the choice of a model of local government on the basis of scientific research of all factors of a particular territory. It is proposed to use the social identity of the population as one of the criteria indicating the possibility of establishing the municipality and defining its territory. The author believes that the social identity of a certain territorial collective, externally expressed, first of all, in the unique self-name of the imaginary community, is the primary and obligatory sign of the presence of a local community. In the absence of a territorial social identity, it makes no sense grant self-government, as there is no self-organisation. Where available, the capacity of the local community for self-government should be examined and developed. To identify the social identity of the population, the author suggests to use the method of sociological survey, as well as the proximity efficiency factor. It is concluded that the methodology of social identity identification should be developed separately.
Keywords: local self-government; local government; identity of population; territorial organisation